IMF Survey, Volume 33, Issue 21. (IMF Survey; IMF Survey ;, 2004)
In early June, Rodrigo de Rato, a national of Spain, took over as head of the IMF, succeeding Horst Kohler, who resigned in early March. Before joining the IMF, de Rato served for nearly eight years in the Spanish government, most recently as Minister of Economy and Vice President for Economic Affairs (2000-2004). He also had a long political career, including a stint as a member of Spain's parliament. Laura Wallace of the IMF Survey spoke with him about the forces shaping the global economic outlook and the ongoing strategic review of the IMF's role.